Novel Approach to Estimating Glacial Moraine Reserves in the Parlung Tsangpo Basin - Wang, Jiao; Cui, Peng; Wang, Hao; Zhang, Guotao; Zou, Qiang; Chen, Xiaoqing (Frontiers in Earth Science, 2022)
The Sichuan–Tibet Railway crosses through the largest maritime glacier region in China. A large number of moraines formed after the rapid glacial retreat caused by climate warming. Moraines could induce frequent geological hazards that seriously threatened the safe construction and operation of the railway. Accordingly, moraines in this maritime glacier region have become a new challenging research topic with respect to the formation of geological hazards. Using remote-sensing image interpretations, field investigations, and dating tests, moraines and their topographic information were systematically obtained. After analyzing the geometrical distribution characteristics of the moraine accumulations, the geometrical characteristics of three typical moraine accumulation forms were generalized into corresponding mathematical models. Consequently, a method to quickly and quantitatively estimate the moraine reserves is proposed. The moraine distribution is primarily affected by the elevation, slope, river–valley morphology, and climate conditions. Old moraines that formed in the Pleistocene epoch (the Guxiang and Baiyu glacial periods) are primarily distributed below 3,500 m above sea level, while most of the new moraines that formed in the Holocene epoch (Neoglaciation and Little Ice Age) are primarily distributed above 4,000 m above sea level. Both the new and old moraines are primarily distributed within a slope range of 10–30°. Furthermore, the main river–valley morphology has a significant impact on the distribution of the old moraines, which are primarily distributed in the Zhongba–Guxiang section of the river valley where the longitudinal slope is relatively gentle. The difference in glaciation is the main reason why the new moraines distributed on the south banks in the study area are different from those on the north banks and why those distributed upstream are different from those distributed downstream. In addition, moraines are the main source of glacial debris flows. According to the presented method, the loose moraine reserves can be accurately calculated by analyzing the position, consolidation, and supply capability of the new and old moraines in each debris flow gully. It is anticipated that the presented results can be used to better understand the formation mechanisms of glacier-related hazards and improve risk assessments.